Yield and profitability of papaya genotypes based on chemical, organic and biological fertilization - Alcantara Jimenez, Jose Angel; Aguilar Carpio, Cid; Leyva Bautista, Silvino; Alcántara Nazario, Ángel Osvaldo (Revista Mexicana de Ciencias Agrícolas, 2019)
Papaya is one of the fruit trees with the greatest demand in world markets, so it is important to develop new agricultural technology (fertilization) that helps to produce papayas of excellent quality, in addition to reducing production costs. The objective of this study was to determine the effect of chemical, organic and biological inoculant fertilization on the yield and profitability of two papaya genotypes. The investigation was carried out in the Superior Agricultural College of the state of Guerrero. The study consisted of evaluating the two genotypes of papaya, Maradol and Mulata in combination with chemical fertilizers, organic and biological inoculants. The evaluated variables were days to flowering, height of plant, stem diameter, days to harvest, number of fruits per plant, diameter and length of the fruit, total soluble solids (°Brix), average weight of the fruit, yield and economic profitability. The genotypes of papaya Maradol and Mulata presented a better response in their growth with the application of chemical fertilizer, for having fewer days to harvest, as well as a larger stem diameter in comparison to biological and organic fertilization. The chemical fertilization in papaya plants Maradol generated the highest number of fruits (38) and content of soluble solids (11.49 °Brix) and in the genotype Mulata promoted a better fruit weight (1 906 g) and yield (99.19 t ha-1). The biological inoculants favor the increase in the size of the fruit. Mulata with chemical fertilization was more profitable (GPI of 5.36) than Maradol with (GPI of 4.98).